The role of green innovation in mediating the influence of artificial intelligence (AI) on purchase intention - Damayanti, Rizki Wahyuning; Sumayyah, Sumayyah (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
The implementation of artificial intelligence has become widespread across various sectors, including marketing. Several previous studies have linked artificial intelligence to innovation and purchase intention across various sectors. This study aims to examine the mediating roles of environmentally friendly product and process innovation in the relationship between artificial intelligence (AI) and purchase intention. This study used quantitative and qualitative methods (mixed methods). Data collection for this study was conducted among 307 Gen Z respondents across Indonesia. The quantitative research employed a questionnaire created in Google Forms, whereas the qualitative research involved direct interviews with respondents. Data collection was conducted only cross-sectionally (i.e., once), with the assumption of representativeness of the period. This study shows that environmentally friendly product and process innovations can mediate the effect of AI on purchase intention